Emotional barriers of adults in learning a foreign language: causes, triggers, and ways to prevent dropout from learning - Kostiuk, Tetiana (Global Prosperity, 2022)
Abstract. Why do adults quit learning a foreign language? Usually not because of grammar. At some point, the fear of saying something wrong, the tension during class, or embarrassment in front of the group becomes stronger than the motivation to continue. For an adult, this anxiety has specific roots: bad experiences at school, the habit of demanding perfect results from oneself, pressure at work. Children treat mistakes lightly - adults see each inaccuracy as failure. The article examines when exactly a person is most likely to drop out: after several months without visible progress, due to disappointment with the course format, or because of memories of previous failures. Several ways to prevent this are proposed: changing the classroom atmosphere, building the program around the student’s real needs, not evaluating every word. Questions for further research are identified separately - how to track the emotional state of adult learners and what specific methods actually help them.